Numerical Investigation of the Effects of Aspect Ratio on the Hydrodynamic Performance of a Semi-Planing Catamaran - Moghaddas AliAsghar; Zeraatgar Hamid (Polish Maritime Research)
A semi-planing catamaran is a type of marine craft that benefits from high speed, in conjunction with the its inherent characteristics such as a large deck and high transverse stability. The aspect ratio, length over the beam of a demi-hull, significantly affects the hydrodynamic performance of this vessel. In this study, the effects of the aspect ratio on the hydrodynamic performance of a semi-planing catamaran in calm water and waves are investigated using numerical simulations. The numerical simulation of the AUT-SEM00 model itself is validated by its model test results. The results show that increasing the aspect ratio significantly increases the wetted surface, and that the increase in resistance in calm water is negligible. In addition, increasing the aspect ratio radically reduces the amplitude of vertical acceleration in waves at the center of gravity by up to 85%. Consequently, the seakeeping performance is considerably improved, and the risk to crew and equipment is reduced.